A New Species of Albizia from Andhra Pradesh - Sarni, K. C.; Bennet, S. S. R. (Indian Forester, 1975)
A new species of Albizia Dura ., A. sikharamensis Sahni and Bennet from Andhra Pradesh is described. Allied to A. amara. Differs in the shape of leaflets. Leaflets puberulous above, mid-vein placed clearly towards the upper margin and pod glabrous and narrower.